The in situ construction of three-dimensional core–shell-structured TiO2@PPy/rGO nanocomposites for improved supercapacitor electrode performance. (4th January 2021) - Li, Shiyun; Zhang, Ling; Zhang, Luxi; Zhang, Jiaoxia; Zhou, Haijun; Chen, Xuecheng; Tang, Tao
Abstract : Three-dimensional core–shell-structured TiO2 @PPy/rGO nanocomposites can be used as ideal electrodes with a longer discharge time and higher capacitance. Abstract : Three-dimensional core–shell-structured TiO2 @PPy/rGO nanocomposites were successfully constructed from TiO2 @PPy nanospheres and graphene oxide via a polymerization method. First, TiO2 nanoparticles were uniformly coated with polypyrrole (PPy), forming core–shell TiO2 @PPy nanospheres. The as-prepared TiO2 @PPy nanospheres further self-assembled with graphene oxide (GO), resulting in the formation of three-dimensional ternary TiO2 @PPy/rGO nanocomposites. Due to the strong interactions between TiO2 @PPy and reduced graphene oxide (rGO), the three-dimensional TiO2 @PPy/rGO electrode exhibited larger specific capacitance, lower charge transfer resistance, and more stable cycling performance compared to the TiO2 @PPy nanospheres. More importantly, the existence of rGO increased the cycling stability of PPy and improved the capacitive performance, thus further demonstrating the positive effects of rGO, achieving a highest specific capacitance of 462.1 F g −1 at a current density of 0.5 A g −1 . The present strategy will pave the way for the development of a new generation of advanced electrode materials for energy storage.